Effect of Statin Therapy In Ventricular Arrhythmias In Patient With Acute Anterior Myocardial Infarction (Cardiovascular Journal, 2013)
Background: Though statins are widely used in acute coronary syndrome (ACS), there is a paucity of information on the efficacy of high dose statin therapy in reducing the incidence of ventricular arrhythmias after acute myocardial infarction. Arrhythmias are relatively common in acute myocardial infarction (AMI) anterior, and sometimes progress to cardiac arrest. This study was planned to evaluate the role of high dose atorvastatin therapy in prevention of ventricular arrhythmias after acute anterior myocardial infarction. Methods: This study was conducted in NICVD from December 2010 to October 2011. Total 200 patients with newly diagnosed acute anterior myocardial infarction who received thrombolytic therapy were included in the study. They were divided into two groups. Group I (n=100) was selected for high dose atorvastatin therapy and group II (n=100) was selected for conventional doses of atorvastatin therapy. 24 hours Holter monitoring was performed 48 hours after hospital admission to evaluate arrhythmia. Results: Majority of the patients belonged to age range of 40 to 59 years with a male predominance. Patient characteristics regarding age, sex, drug use, risk factors for ventricular arrhythmia, body mass index, left ventricular ejection fraction were similar in two study groups. There was no electrolyte imbalance or renal impairment in any patient in either group. A significant difference in frequency of ventricular arrhythmias was found between the two groups. Ventricular premature beats were found in 66% patients in group I and 97% patients in group II (p=0.001) whereas non sustained ventricular tachycardia were observed in 0% and 4% in group I and group II respectively. Conclusion: High dose atorvastatin therapy is associated with lower frequency of ventricular arrhythmias after acute anterior myocardial infarction. Cardiovascular Journal Volume 6, No. 1, 2013, Page 37-42 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16113